2019
DOI: 10.1128/mbio.02662-18
|View full text |Cite
|
Sign up to set email alerts
|

Didehydro-Cortistatin A Inhibits HIV-1 by Specifically Binding to the Unstructured Basic Region of Tat

Abstract: Tat activates virus production, and limited Tat transactivation correlates with HIV-1 latency. The Tat inhibitor dCA locks HIV in persistent latency. This drug class enables block-and-lock functional cure approaches, aimed at reducing residual viremia during therapy and limiting viral rebound. dCA may also have additional therapeutic benefits since Tat is also neurotoxic. Unfortunately, Tat inhibitors are not clinically available. We generated chemical derivatives and rationalized binding to an active and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 64 publications
1
51
0
Order By: Relevance
“…However, large-scale dCA production may be difficult [100], which could limit its availability. As the molecular interaction between dCA and Tat has been modeled [74], a future in silico screening project using pharmacophore based models of dCA interaction with Tat may identify additional agents with anti-Tat activity. Drug repurposing of the rheumatoid arthritis drug triptolide as an HIV inhibitor awaits safety and efficacy outcomes in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, large-scale dCA production may be difficult [100], which could limit its availability. As the molecular interaction between dCA and Tat has been modeled [74], a future in silico screening project using pharmacophore based models of dCA interaction with Tat may identify additional agents with anti-Tat activity. Drug repurposing of the rheumatoid arthritis drug triptolide as an HIV inhibitor awaits safety and efficacy outcomes in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…dCA also specifically bound to the basic domain of HIV-2 Tat [73] and SIV Tat [76]. The binding of dCA to the basic domain of Tat occurred across HIV subtypes A to E in the main group M [104], but dCA did not bind to the basic domain of Rev and HEXIM1 [74]. dCA caused a redistribution of Tat in the nucleus from the nucleolus to the nucleoplasm and periphery of the nucleolus in a dose-dependent manner [73].…”
Section: Two Compounds That Inhibit Tat Activitymentioning
confidence: 99%
“…On the other hand, the kinase module (composed of two subunits Med12 and Med13 and the kinase CDK8, or its paralog CDK19) are thought to be dispensable for HIV-1 transcription [136]. This is evidenced by small molecule inhibition or knockdown of these proteins in cell line models of HIV-1 latency [138,139]. Additional research would benefit our understanding of the role of mediator in HIV-1 PIC formation, initiation and elongation, particularly in biologically relevant systems such as primary CD4 + T cells.…”
Section: Early Stages Of Transcriptionmentioning
confidence: 99%
“…CDK8 generally plays a suppressive role as part of the mediator complex, though it is known to activate transcription of certain cellular genes [150]. Importantly, it was recently demonstrated that knockdown of CDK8 (and its paralog CDK19) had no effect on HIV-1 transcription [138,139]. CDK12/CDK13 has been shown to be involved in Ser2 phosphorylation towards the midpoint and 3' ends of genes, and play a role in RNA processing and splicing [143,151,152].…”
Section: Early Stages Of Transcriptionmentioning
confidence: 99%
“…We next investigated whether dCA binds the basic domain of SIV mac 239 Tat, as it does for HIV Tat (19,37). A biotinylated version of dCA, which has similar IC 50 against HIV than dCA (19), was used for pull-down assays, in combination with streptavidin-coated beads of transfected Tat proteins.…”
Section: Dca Binds To Siv Tat Basic Domainmentioning
confidence: 99%